2014
DOI: 10.1016/j.artres.2014.09.124
|View full text |Cite
|
Sign up to set email alerts
|

P4.1 Impact of Age and Gender on the Determinants of Pulse Pressure and Isolated Systolic Hypertension

Abstract: Background: Research shows an association between particulate air pollution exposure and cardiovascular morbidity and mortality, with atherosclerosis as an implied underlying mechanism. The accurate assessment of personal exposure is a major challenge in epidemiological research since it is strongly related to time-activity patterns. We investigated carotid intima-media thickness (CIMT) in association with subchronic personal exposure to black carbon (BC) in a panel of healthy adults. Methods: Personal BC expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This approach was superior to the approach used in the previous study (25), which used risk ratios to analyze the prevalence (only in 2005) and incidence (2006–2008) of hypertension in patients with major depression. In the proportional hazards model analysis of the total cases, the results of our study were similar to previous research (48, 49), with male and older subjects having a higher rate of hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…This approach was superior to the approach used in the previous study (25), which used risk ratios to analyze the prevalence (only in 2005) and incidence (2006–2008) of hypertension in patients with major depression. In the proportional hazards model analysis of the total cases, the results of our study were similar to previous research (48, 49), with male and older subjects having a higher rate of hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…(14) Data from the Anglo-Cardiff Collaborative Trial II study suggested that the CASP cut-off value might approximate 125 mmHg; this value was 'translated' from the usual 140/90 mmHg brachial SBP cut-off for healthy and treatment-naïve hypertensive persons. (3) We acknowledge that there was a lack of a comparative or control arm in the present study; we demonstrated only the pre-and post-effect of valsartan treatment on CASP. This weakness, which would have led to a regression artefact, could have resulted in overestimation of the treatment effect of valsartan.…”
Section: Discussionmentioning
confidence: 92%
“…While it is true that brachial SBP is generally higher than CASP and a relatively high correlation exists between the two, we cannot predict the degree of BP amplification with accuracy using statistical calculations. (2,3) This is because pulse wave reflection is affected by arterial compliance, and factors such as age, height, heart rate and type of drug used. It has also been reported that different drugs have differential effects on CASP beyond peripheral BP lowering.…”
Section: Introductionmentioning
confidence: 99%